WYKORZYSTANIE NOWYCH MEDIÓW W KONTEKŚCIE POPRAWY JAKOŚCI ŻYCIA POLSKICH SENIORÓW - Zychowicz, Maciej (Rocznik Pedagogiczny, 2018)
Subject of the report is media exclusion of elderly people in Poland, especially in area of Inter- net-connected activities as well as changes in social interaction model which are connected with development of the Internet. Nowadays we face with Internet revolution witch whom technological progress and web tools development allowed to partly virtualize interpersonal contacts and change the way people interact with others. Even in area of everyday life the Internet revolution allowed to modify our behaviors which were immutable from ages.The aim of this report is to assess the level of inclusion of the elderly people from Poland into area od virtual contacts and other activities as well as presenting their methods to use different media.